CREATION OF PRECONDITIONS FOR THE DEVELOPMENT OF INNOVATIVE ACTIVITY BASED ON THE FORMING OF ORGANIZATION MANAGEMENT STRUCTURE - N. Maslennikova (Publishing House of the State University of Management, 2016)
The article contains the methods of analysis of the management structure on the example of a specific organization. The criterion of the analysis and projection is the consistence of the organizational characteristics with the concept of innovation management. In details revealed the consequence of the steps of the analysis and projection of the management structure that create the preconditions for development of the innovative potential and the growth of the innovative activate of the organization personal. The conclusions are made about the necessity of the new organizational characteristics: organist type of the interaction with the external environment, individual type of relationship to person, resource-result criteria of department division, implementing of the elements of the matrix structure, competence and universalization of the specialists that works in project cross-functional teams, decreasing hierarchy levels, enhance the flatness of the structure as a result of greater openness and awareness, decentralization of the main management functions, centralization of the functions of the general management, creation of the management functions aimed to the correlation with the external environment